Multi-modality Optometric Treatment of Deep Amblyopia Secondary to Micro-esotropia and Anisometropia. - Cao, Judy; Giebel, Jana; Tong, Derek (Optometry & Visual Performance, 2017)
Background: Amblyopia is a reduction in visual acuity that often involves reduction in visual skills such as ocular motility and accommodation. Various treatment modalities for amblyopia include spectacle correction, patching, atropine, and optometric vision therapy (OVT). Clinically, OVT often reduces the severity of amblyopia. There is also considerable anecdotal evidence that improvement in amblyopia and its related visual deficiencies can be achieved at almost any age. Case Report: A nine-year-old Caucasian male was referred by his primary care optometrist for amblyopia treatment. Previous treatment included full-time prescription lenses and part-time direct patching for 3½ years. Our evaluation found deep amblyopia secondary to anisometropia, micro-esotropia, and eccentric fixation. A visual evoked potential (VEP) was obtained to estimate his potential visual acuity and to rule out optic pathway defect. The SHAW lens, officebased vision therapy, home-based syntonics, and home-based Amblyopia iNet and Perceptual Visual Tracking programs were prescribed, and the patient continues to show good progress. Conclusion: A multi-modality treatment approach provided a good functional outcome for this patient with deep amblyopia secondary to constant esotropia and anisometropia. The multi-modality treatment for this patient included spectacle lenses, as well as OVT and home-based vision therapy, for optimal results.